THE EFFECT OF ENVIRONMENTAL DISCLOSURE AND ENVIRONMENTAL PERFORMANCE ON PROFITABILITY IN COMPANIES IN THE CONSUMER GOODS INDUSTRY SECTOR THAT LISTED ON THE INDONESIA STOCK EXCHANGE PERIOD 2020-2023 - Ginting , Arie Tymoty Rainaldo; Ginting, Mitha Christina; Sagala, Farida; Simanjuntak, Arthur (Jurnal Ilmiah Accusi, 2025)
This comprehensive study explores the strategic dimensions of the relationship between environmental disclosure, environmental performance, and profitability in the Indonesian consumer goods industry sector. The research focuses on an in-depth analysis of companies listed on the Indonesia Stock Exchange, aiming to uncover the complex mechanisms by which environmental sustainability practices influence organizational financial performance. The research methodology employs a quantitative approach using purposive sampling technique, where out of 51 potential entities in the population, researchers selected 12 companies as analysis units. Data access was conducted through the official platform www.idx.co.id, utilizing multiple linear regression statistical analysis to explore correlations between variables. Empirical findings yield significant insights. Environmental disclosure demonstrates a substantial positive correlation with profitability, indicating that environmental transparency can serve as a strategic instrument for enhancing a company's economic value. In contrast, environmental performance displays a negative relationship inconsistent with profit levels, signaling the complexity of dynamics between environmental practices and financial efficiency. Simultaneous analysis reveals that environmental disclosure and performance variables collectively exert a significant influence on profitability. The coefficient determination test shows that the research model can explain 18.6% of profitability variation, with the majority 81.4% influenced by external factors not yet identified within the research framework. The primary contribution of this study lies in developing a contextual understanding of the interconnection between environmental responsibility and corporate economic performance, offering novel perspectives in strategic management and business sustainability literature